Decorrelation is not dissociation: There is no means to entirely decouple the Brutsaert-Nieber parameters in streamflow recession analysis. (January 2021) - Biswal, Basudev
Abstract: The coefficient of the Brutsaert-Nieber equation cannot provide information on streamflow dynamics independently because its value depends on the exponent. One way to address this challenge is to compute the coefficient after fixing the exponent, which may involve fitting errors. A recent study has therefore adopted a method to decorrelate the coefficient from the exponent. Here, I argue that the decorrelation method does not dissociate the Brutsaert-Nieber parameters or make them independent of each other. Analysis of real and synthetic recession curves suggests that for a wide variety of scenarios the fixed exponent method is preferable to the decorrelation method.